Understanding depression and role of rehabilitation among the visually impaired: a pilot study - F. Khurshid; H. Pandey; A. Singh (Российский офтальмологический журнал, 2025)
The increasing cases of low vision and blindness have been associated with negative impact on the mental health and quality of life of the person by many researches. Rehabilitation plays a key role in making the patient learn to utilize their potential vision to readjust and function as a part of the society. There are many factors that may play a vital role in causing depression among the visually impaired and this pilot study tries to understand and describe the role of these factors to enable the practitioners to device an appropriate rehabilitation plan for the patient. The purpose of this pilot study was to understand depression in visually impaired people, as well as the function of rehabilitation in mitigating its consequences to structure further research in this field. Material and methods. The Hospital Anxiety and Depression (HAD) questionnaire was administered to 30 visually impaired patients (17 females and 13 males of age 18 and above) diagnosed with blindness (VA < 3/60) or low vision (VA < than 6/18 in the better eye and/or visual field up to 20 degrees in better eye) after obtaining their consent. The study evaluated the relationship between depression and a variety of parameters such as the type and onset of visual impairment, rehabilitation services, type and duration of visual rehabilitation and psychological counselling. Mean depression scores were calculated and compared for each category using SPSS. Results. According to some of the major findings of this study, multimodal rehabilitation surely has an important impact in lowering depression among visually impaired people. The group that received services involving the use of low visual aids had a mean depression score of 12.00 ± 3.381 while the group that received multidisciplinary rehabilitation services had a mean depression score of 7.20 ± 6.861 (p-value 0.074). Furthermore, psychological counselling was proven to be effective in treating depression in this population. The mean depression score of the group that didn’t receive any psychological counselling was significantly higher with a value of 12.60 ± 5.835 in comparison to the group that received psychological counselling having a mean depression score of 5 ± 3.33 (p-value 0.001). Conclusion. This pilot study concludes that visual impairment is associated with depression and rehabilitation can play an important role in lowering its incidence. Moreover, a multimodal approach can prove beneficial and should be adopted by the eye care practitioners. Psychological counselling should be made mandatory for the patients with visual impairment at the time of receiving a diagnosis and well as throughout the course of treatment and rehabilitation.